A Behavioral Study of Cylindrical Object Impacted by Bullet Using FEA - Saisueb, Tanadon; Woraratsoontorn, Pattaraweerin (International Journal of Natural Sciences Research, 2018)
Crime news has now become a popular mass media topic with offenders often using pocketknives and firearms. Pocketknives are inexpensive and easily obtained while in Thailand firearms have also become readily available. Some people are lucky and survive gunshot wounds; articles carried in their shirt pockets, especially a metal pen, may increase survival chances. Deformation behavior of a cylindrical object and a stainless steel pen impacted by a 9 mm FMJ (full metal jacket) bullet were investigated under various conditions. Finite element analysis (FEA) was applied to simulate different shooting conditions. Comparison of FEA shooting test simulation results revealed that a cylindrical object and stainless steel pen behaved in a similar manner. Simulation results can be useful to support forensic science examinations. Analysis of the findings indicated that having a stainless steel pen in your shirt pocket may improve the chances of surviving a bullet wound.